Analyzing Speech Acts in Peer Interaction Among EFL High School Students - Rafiah, Hafidatur; Khodijah, Siti; Madeeyoh, Na-a (Journal of Language Intelligence and Culture, 2025)
This study explores the use of speech acts among high school students during peer discussions in an English as a Foreign Language classroom. It aims to identify the types of illocutionary acts students produce and understand how they employ language to negotiate meaning and express ideas in peer interaction. The research was conducted at MAN 1 Jember with four students from the Bina Insan Cendekia program, using a qualitative descriptive design. The previous research was conducted at elementary scholl or junior high school, and in this study researcher conducted in senior high choll to fulfill the gap in this field. Data were collected through audio recordings, observations, and transcripts of peer discussions on the topic of mental health. The analysis, based on Searle’s speech act theory, revealed that assertive acts were most frequently used, followed by expressive, directive, and commissive acts, while declarative acts were absent. Students used assertive acts to share experiences and state opinions, expressive acts to convey emotions and reactions, and directive acts to maintain the flow of conversation. Commissive acts were rare and typically appeared in supportive or empathetic responses. The results highlight the significance of topic relevance and peer familiarity in encouraging authentic language use. This study contributes to understanding pragmatic competence in EFL settings and supports the use of peer discussion as a valuable strategy for enhancing speaking skills and meaningful communication in the classroom.